Strategy for applying utility model patents in clinical nursing (临床护理用具实用新型专利申请心得体会) - QIAO Shouang (乔首昂); WANG Shuo (王烁); PEI Xiaolu (裴晓璐) (Association of Integrative Nursing, 2021)
This paper summarized the strategy for applying utility model patents in clinical nursing. Issues about meaning of patent, application procedure and design inspiration were discussed and shared, in order to provide reference in design and application of utility model patents for clinical nurses. (本文总结临床护理用具实用新型专利申请过程中的相关经验, 包括专利的含义、专利申请流程、专利设计灵感等, 希望以此为广大临床护理工作者在研发和申请专利方面提供可靠参考。)